How frequently do consumer prices change in Austria? Evidence from micro CPI data - Josef Baumgartner; Ernst Glatzer; Fabio Rumler; Alfred Stiglbauer (European Central Bank (ECB), 2005)
Based on individual price records collected for the computation of the Austrian CPI, average frequencies of price changes and durations of price spells are estimated to characterize price setting in Austria. Depending on the estimation method, prices are unchanged for 10 to 14 months on average. We find strong heterogeneity across sectors and products. Price increases occur only slightly more often than price decreases. The typical size of a price increase (decrease) is 11 (15) percent. The aggregate hazard function of prices is decreasing with time. Besides heterogeneity across products and price setters, this is due to oversampling of products with a high frequency of price changes. Accounting for unobserved heterogeneity in estimating the probability of a price change with a fixed-effects logit model, we find a positive effect of the duration of a price spell. During the Euro cash changeover the probability of price changes was higher.
Keywords: C41; D21; E31; L11; 330; consumer prices; duration of price spells; frequency and synchronization of price changes; sticky prices; Verbraucherpreisindex; Preisniveau; Preisrigidität; Schätzung; Österreich